Development of A “Cheerful Engklek Carpet” Game as A Learning Medium to Enhance Spatial Intelligence in Early Childhood - Mai Mutiah Tri Wahyuni; Nita Priyanti; Chandra Apriyansyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Spatial intelligence is a fundamental ability that needs to be developed from an early age; however, its stimulation remains limited due to the lack of learning media that integrate visual, kinesthetic, and cognitive aspects. This study aims to: (1) develop the Cheerful Engklek Carpet game to stimulate spatial intelligence in early childhood, (2) examine the feasibility of the game, and (3) test its effectiveness in enhancing children’s spatial intelligence. This research employed a Research and Development (R&D) method using a modified 4D model (Define, Design, Develop, Disseminate). The subjects consisted of 48 children aged 5–6 years at TK Plus Tunas Rimba, Purwakarta Regency, divided into an experimental group (24 children) and a control group (24 children). Data were collected through expert validation, observation, interviews, and spatial intelligence tests, and analyzed using descriptive and inferential statistics (independent and paired sample t-tests). The results indicate that the developed game is highly feasible (4.65), practical (4.41), and well-implemented (95.6%). It is also highly effective, with a 49.6% improvement in the experimental group compared to 7.0% in the control group (p < 0.001; Cohen’s d = 2.92). In conclusion, the Cheerful Engklek Carpet game is highly feasible and effective in holistically stimulating spatial intelligence in early childhood.